2013
DOI: 10.1021/jm400048v
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Structure Modifications of Multitarget Prostate Cancer Drug Candidate Galeterone To Produce Novel Androgen Receptor Down-Regulating Agents as an Approach to Treatment of Advanced Prostate Cancer

Abstract: As part of our program to explore the influence of small structural modifications of our drug candidate, 3β-(hydroxy)-17-(1H-benzimidazol-1-yl)-androsta-5,16-diene (galeterone, 5) on the modulation of the androgen receptor (AR), we have prepared and evaluated a series of novel C-3, C-16 and C-17 analogs. Using structure activity analysis, we established that the benzimidazole moiety at C-17 is essential and optimal and also that hydrophilic and heteroaromatic groups at C-3 enhance both anti-proliferative (AP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 75 publications
3
88
0
5
Order By: Relevance
“…1c). The calculated IC50 for LNCaP cells (5.6±0.8 µM; n=4) was comparable to that published by other authors using end-point cytotoxicity assays (between 1 and 5 µM) 9,10 . In contrast, the calculated IC50 value for PC-3 cells had to be extrapolated up to a non-physiological value (34.9±9 µM; n=4).…”
Section: Estimation Of Enzalutamide Ic50s On Two Human Metastatic Prosupporting
confidence: 86%
“…1c). The calculated IC50 for LNCaP cells (5.6±0.8 µM; n=4) was comparable to that published by other authors using end-point cytotoxicity assays (between 1 and 5 µM) 9,10 . In contrast, the calculated IC50 value for PC-3 cells had to be extrapolated up to a non-physiological value (34.9±9 µM; n=4).…”
Section: Estimation Of Enzalutamide Ic50s On Two Human Metastatic Prosupporting
confidence: 86%
“…As mentioned above, the CYP17A1 inhibitor galeterone not only inhibits the enzyme but is also a competitive AR antagonist and causes degradation of the AR and its variants AR-V7 and Arv567es [153,[166][167][168] . Furthermore, galeterone also impaired AR binding to DNA and selectively up-regulated degradation of the mutated T878A AR protein [122,123] .…”
Section: Bifunctional Inhibitors and Antagonists Targeting The Ar Axismentioning
confidence: 98%
“…Preclinical in vitro and in vivo data have shown that galeterone treatment in prostate cancer models resulted in a significant reduction in both full-length AR and AR-V7 splice variant levels. In addition, galeterone has been shown to have activity against AR point mutations T878A (20)(21)(22)(23)(24)(25) and, in preliminary findings, to have activity in cells expressing the AR point mutation F876L (27).…”
Section: Introductionmentioning
confidence: 97%
“…Preclinical data have shown that galeterone is a selective potent CYP17 inhibitor and a potent AR antagonist, but unlike other available agents that target androgen signaling, galeterone reduces AR expression in prostate cancer cells by causing an increase in AR protein degradation (20)(21)(22)(23)(24)(25)(26). Preclinical in vitro and in vivo data have shown that galeterone treatment in prostate cancer models resulted in a significant reduction in both full-length AR and AR-V7 splice variant levels.…”
Section: Introductionmentioning
confidence: 99%